Effect of Partial Root Drying on Yield and Fruit Quality of Melons (Cucumis Melon, L. Var. Glamour) - Fatahian, Vahid Aldin (2010)
Growth, productivity and fruit quality of melons are closely linked to media water availability. Withholding of water for any length of time results in slowed growth. If drought continues yield may be lost. Melon plants can be manipulated to stimulate early defense mechanism by deceasing media water availability. By using an irrigation technique, which allows for separate zones with different media moisture status, it is possible to stimulate response mechanisms of the root system which are normally related to water stress. The difficulty of separating ‘wet’ and ‘dry’ zones was initially overcome by using split-root plant with root systems divided between two containers. Such experiments on split-root model plant resulted in the development of an irrigation technique termed partial root drying (PRD). The main objective of the study was to determine the effects of partial root drying (PRD) on the growth and physiological responses of melon plants. It was hypothesized that PRD-exposed plants would enhance their quality and water use efficiency. In this study, three experiments were conducted to meet the following objectives, 1) to investigate the effects of PRD interval and deficit irrigation (DI) on plant yield and quality. 2) to study the effects of different PRD irrigation and nutrient levels on growth, leaf gas exchange, macro and micro nutrients status of melons and 3) to examine the effects of PRD fertigation deficiency on growth and yield of plants. In experiment one, melon plants were exposed to different PRD interval viz full irrigation (control), deficit irrigation (50% of full irrigation), PRD 2, 4, 6, 8 and 10 days interval. Results showed that deficit irrigation had the most reduction in yield when compared to PRD and fully irrigated treatments. When the shifting time in PRD treatments increased to 8 and 10 days, the fruit yield was significantly reduced compared to the control and PRD 2, 4, 6 days interval. Total number of flower in full irrigation treatments was significantly higher than PRD and DI plants. There was no significant difference in number of flowers between PRD 2, 4 and 6. Total soluble solids (TSS) of PRD 8 and 10 days interval was the highest among the PRD, DI and control treatments. In the second experiment, melon plants were subjected to different irrigation and nutrient levels viz PRD 100%, 80%, 70% and 60% of full irrigation (FI), PRD 70% and 100% of full nutrients (FN). Results showed that there was a significant difference between media volumetric moisture amounts of irrigation levels during experiment. There was no significant difference between RWC of different irrigation levels, although the RWC amount of PRD 80%, 70% and 60% of FI was numerically less than control plants. By reducing the amount of water, LAI value significantly declined in different levels of PRD irrigation treatments. Total leaf nitrogen (N) was significantly (p≤0.01) declined in PRD 80%, 70% and 60% of FI, compared to control plants. However, there was no significant difference between PRD70% and 60% of FI. There was a significant interaction between irrigation and nutrient levels on photosynthesis rates (Pn). Stomata conductance value of FI was the highest and PRD 60% of FI were the lowest value compared to PRD 70% and 80% of FI. There was a significant interaction between irrigation and nutrient levels on water use efficiency (WUE). There was a significant interaction between irrigation and nutrient levels on yield. The highest amount of TSS was observed in PRD 60% of FI. In the third experiment, plants were exposed to PRD fertigation deficit viz: PRD 100% of FI (control), PRD 90%, 80%, 70% and 60% of FI. The treatments were arranged in RCBD and replicated four times. The results showed that there was a significant difference between the root to shoot ratio of PRD 100%, 90%, 80%, 70% and 60% of FI in 10, 20, 30 and 40 days after treatment. There was a significant relationship between NAR and Pn in PRD 80% and 100% of FI (p≤0.01). The results also indicated that the fruit fresh weight of PRD 90%, 80%, 70% and 60% of FI were 5%, 4%, 10% and 18% less than control plants, respectively. In conclusion, PRD two days interval with 80 % of FI and 100 % of FN could improve melon fruit quality with a little adverse effect on yield compared to control.